"Safariland": Tourism, Development and the Marketing of Kenya in the Post-Colonial World. (28th May 2018) - Smart, Devin
Abstract: This article explores the role of tourism in the development plans of Kenya during the 1960s and 1970s, examining what this reveals about the new opportunities and constrictions that officials encountered as they tried to globally reconfigure the place of their new decolonizing nation in the post-colonial world. These themes are explored by examining the political economy of development and tourism, the marketing infrastructures that Kenyan officials created to shape how Western consumers thought about "Kenya, " and how these factors influenced the kinds of discourses that were promoted globally about this newly-independent African country. Résumé: Cet article explore le rôle du tourisme dans les plans de développement du Kenya au cours des années 1960 et 1970, et examine ce que cela révèle sur les nouvelles possibilités et restrictions rencontrés par les officiels alors qu'ils tentaient de reconfigurer globalement la place de leur nouvelle nation décolonisée dans le monde postcolonial. Ces thèmes sont explorés par le biais d'un examen de l'économie politique du développement du tourisme, des infrastructures de commercialisation créées par les fonctionnaires kényans pour façonner l'impression occidentale du « Kenya », et comment ces facteurs ont influencé les types de discours qui ont été promu à l'échelle mondiale au sujet de ce pays d'Afrique nouvellement indépendants.